Primary testicular lymphoma: a single centre experience - Kemal, Y.; Teker, F.; Demirag, G.; Yucel, I. (Experimental Oncology, 2015)
Aim: Primary testicular lymphoma (PTL) is an uncommon and aggressive form of extranodal non-Hodgkin’s lymphoma (NHL). We aimed to analyse the clinicopathological characteristics and outcomes of our PTL cases. Materials and Methods: A review was made of the medical records of 339 NHL patients who were treated in the Medical Oncology Department between January 2005 and December 2013. Results: 8 PTL patients were identified from the 339 NHL patients. The average age of the patients was 67.7 ± 7.9 years (range 53–79 years). The mean follow-up time was 24.8 months (range 7–98 months). Inguinal orchiectomy was performed as a diagnostic and initial therapy and all the patients underwent 4–6 cycles of chemoimmunotherapy consisting of cyclophosphamide, doxorubicin, vincristine and prednisone plus rituximab. 4 of 8 patients received intrathecal prophylactic chemotherapy and 6 of 8 patients continued contralateral testis irradiation. Relapse occured in only 1 patient in central nervous system after 6 months who had not received intrathecal prophylaxis. No contralateral testis relapse was observed. Conclusions: Primary testicular NHL is an uncommon entity and we evaluated 8 patients; with one relapse in central nervous system and no relapse in the contralateral testis. Key Words: primary testicular lymphoma, contralateral scrotal irradiation, intratechal chemotherapy.